2017
DOI: 10.1021/acs.orglett.6b03359
|View full text |Cite
|
Sign up to set email alerts
|

Iron Complex Catalyzed Selective C–H Bond Oxidation with Broad Substrate Scope

Abstract: The use of a peroxidase-mimicking Fe complex has been reported on the basis of the biuret-modified TAML macrocyclic ligand framework (Fe-bTAML) as a catalyst to perform selective oxidation of unactivated 3° C-H bonds and activated 2° C-H bonds with low catalyst loading (1 mol %) and high product yield (excellent mass balance) under near-neutral conditions and broad substrate scope (18 substrates which includes arenes, heteroaromatics, and polar functional groups). Aliphatic C-H oxidation of 3° and 2° sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…This result is consistent with a similar oxidation reported by us using complex 1 and mCPBA as the oxidant. 19 Furthermore, the regioselective oxidation of 3° C–H bonds in the natural product derivative of cedrol, cedryl acetate, was performed. Cedrol is a sesquiterpene alcohol found in essential oil, having a very rigid structure with five 3° C–H positions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with a similar oxidation reported by us using complex 1 and mCPBA as the oxidant. 19 Furthermore, the regioselective oxidation of 3° C–H bonds in the natural product derivative of cedrol, cedryl acetate, was performed. Cedrol is a sesquiterpene alcohol found in essential oil, having a very rigid structure with five 3° C–H positions.…”
Section: Resultsmentioning
confidence: 99%
“…However, the photochemical hydroxylation of unactivated C–H bonds using the [Fe II (MePy 2 tacn)] 2+ complex described above has not been reported. Mechanistic studies on iron-catalysed hydroxylation reactions have revealed that in both chemical and biological systems, efficient and selective hydroxylation of unactivated C–H bonds has been mostly catalysed by reactive intermediates such as oxoiron( v ) (synthetic systems), 14 , 15 , 19 the isoelectronic oxoiron( iv ) radical cation (heme enzymes) 4a , 11c , d and [(μ-O) 2 Fe IV 2 ] (methane monooxygenase 11a , b ). None of these intermediates have been formed in the photochemical systems reported to date using [Fe II (N 4 Py)] 2+ and [Fe II (MePy 2 tacn)] 2+ complexes, which explains the absence of iron catalysts being used to catalyse photochemical C–H bond oxidation in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gupta demonstrated that a TAML ligand also can be employed in site‐selective oxidation reactions (Scheme ) . The polyfunctional compound 7 gave the tertiary alcohol a the oxidation product despite the presence of several other oxidizable CH groups present in the molecule.…”
Section: Oxygenations Of Hydrocarbonsmentioning
confidence: 99%
“…Oxidation of CÀ H bonds catalyzed by [Fe III ( NO2 bTAML)(Cl)] 2À . [38] Figure 4. TPA, TPA-derivatives, PyTACN, 6-Me-PyTACN and BPMEN ligands [41,43] along with a schematic representation of their coordination around the iron(II) center.…”
Section: Oxo-hydroxo-iron(v) Speciesmentioning
confidence: 99%